Are Cerebral White Matter Lesions Related to the Presence of Bilateral Internal Carotid Artery Stenosis or to the Length of Stenosis Among Patients With Ischemic Cerebrovascular Events? - Elhfnawy, Ahmed Mohamed; Volkmann, Jens; Schliesser, Mira; Fluri, Felix (Frontiers in Neurology, 2019)
Background and purpose: Previous studies delivered contradicting results regarding the relation between the internal carotid artery stenosis (ICAS) and the white matter lesions (WMLs). We hypothesize that special characteristics related to the ICAS might be related to the WMLs, and hence explain the contradicting results. We examined the relation between the presence of bilateral ICAS as well as the degree and length of stenosis and ipsi-, contralateral as well as mean white matter lesion load (MWMLL). Methods: In a retrospective cohort, patients with ischemic stroke or transient ischemic attack (TIA) as well as ipsi- and/or contralateral ICAS were identified. The length and degree of ICAS, as well as plaque morphology (hypoechoic, mixed or echogenic), were assessed on ultrasound scans and if available, the length was also measured in the magnetic resonance angiography (MRA) and/or digital subtraction angiography (DSA). The WMLs were assessed in 4 sites separately, periventricular and deep WMLs on each side, using the Fazekas scale and the MWMLL was calculated as the mean of these four values. Results: One-hundred-thirty-six patients with 177 ICAS were identified. A strong positive correlation between age and MWMLL was observed (Spearman correlation coefficient, ρ=0.41, p<0.001). Before adjusting for other risk factors, a significantly positive relation was found between the presence of bilateral ICAS and MWMLL (p=0.039). The length but not the degree of ICAS showed a very slight trend toward association with ipsilateral WMLs and with MWMLL. In an age-adjusted multivariate logistic regression with MWMLL ≥2 as the outcome measure, female sex (OR 3.11, 95% CI 1.19-8.11, p=0.02) and diabetes mellitus (OR 2.76, 95% CI 1.16-6.53, p=0.02) were significantly related to WMLs, whereas the presence of bilateral stenosis showed a considerable trend toward significance (OR 2.25, 95% CI 0.93-5.45, p=0.074). No relation was found between plaque morphology and MWMLL, periventricular or deep. Conclusion: Specific characteristics of ICAS may be related to WMLs, which may explain the contradictory results of previous studies. Specifically, the presence of bilateral ICAS seems to be related to the WMLs. It seems that a weak relation exists between the length of stenosis and the WMLs.